The Effect of Person-Job Fit on Turnover Intention Mediated by Work-Family Conflict and Work Engagement in Fast Food Restaurant Employees in East Jakarta - Muhammad Fachri Dilham Welham; Netania Emilisa; Muhammad Fahmi Akbar Siregar (Journal of Social Science, 2024)
This research aims to identify the influence of Person-Job Fit on Turnover Intention which is mediated by Work-Family Conflict and Work Engagement in fast food restaurant employees in East Jakarta. Using correlational research methods and hypothesis testing, this research involved 110-220 respondents selected through purposive sampling techniques. Data was collected through questionnaires and analyzed using Structural Equation Model (SEM) with AMOS software. The research results show that Person-Job Fit has no direct effect on Turnover Intention. However, there is a negative influence between Person-Job Fit on Work-Family Conflict and a positive influence on Work Engagement. Apart from that, Work-Family Conflict has a positive effect on Turnover Intention, while Work Engagement has a negative effect on Turnover Intention. This research provides insight for companies regarding the importance of match between job and employee to increase loyalty and reduce employee turnover intentions.